Refeeding syndrome in the frail elderly population: prevention, diagnosis and management - Aubry, Emilie (Clin Exp Gastroenterol, 2018)
Aging is linked to physiological and pathophysiological changes. In this context, elderly patients often are frail, which strongly correlates with negative health outcomes and disability. Elderly patients are often malnourished, which again is an independent risk factor for both frailty and adverse clinical outcomes. Malnutrition and resulting frailty can be prevented by adequate nutritional interventions. Yet, use of nutritional therapy can also have negative consequences, including a potentially life-threatening metabolic alteration called refeeding syndrome (RFS) in high-risk patients. RFS is characterized by severe electrolyte shifts (mainly hypophosphatemia, hypomagnesemia and hypokalemia), vitamin deficiency (mainly thiamine), fluid overload and salt retention leading to organ dysfunction and cardiac arrhythmias. Although the awareness of malnutrition among elderly people is well established, the risk of RFS is often neglected, especially in the frail elderly population. This partly relates to the unspecific clinical presentation and laboratory changes in the geriatric population. The aim of this review is to summarize recently published recommendations for the management of RFS based on current evidence from clinical studies adapted with a focus on elderly patients.